Studies on Working Qualities of Indian Timbers - Rawat, B. S.; Rajput, S. S.; Pant, B. C. (Indian Forester, 1976)
This is in continuation of the earlier papers (3, 4) by the authors in which working qualities of nine species were given. Following the same procedures, the working qualities of ten more species viz. Acacia catechu, Acer oblongum, Cinnamomum camphora, Dipterocarapus turbinatus, Grevillea robusta. Lagerstroemia speciosa. Morus alba, Shorea rob-usta, Terminalia arjuna and Terminalia alata have been reported in this paper. On the basis of the quality of the worked surface obtained after different operations and ease of working, a working quality index has been obtained for an overall comparison of the species.